2002
DOI: 10.1038/sj.bjc.6600625
|View full text |Cite
|
Sign up to set email alerts
|

Role of genetic polymorphisms in tumour angiogenesis

Abstract: Angiogenesis plays a crucial role in the development, growth and spread of solid tumours. Pro-and anti-angiogenic factors are abnormally expressed in tumours, influencing tumour angiogenesis, growth and progression. Polymorphisms in genes encoding angiogenic factors or their receptors may alter protein expression and/or activity. This article reviews the literature to determine the possible role of angiogenesis-related polymorphisms in cancer. Further research studies in this potentially crucial area of tumour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
49
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 80 publications
1
49
0
Order By: Relevance
“…1 VEGF is strongly expressed in human solid tumours 2 and plays an important role in their pathogenesis. 3 There is evidence that tumours can promote VEGF production in adjacent stroma, which in turn predisposes to further tumour growth.…”
mentioning
confidence: 99%
“…1 VEGF is strongly expressed in human solid tumours 2 and plays an important role in their pathogenesis. 3 There is evidence that tumours can promote VEGF production in adjacent stroma, which in turn predisposes to further tumour growth.…”
mentioning
confidence: 99%
“…Genetic alterations, such as point mutations, have been identified in FGFR genes and have been linked to developmental defects as well as neoplastic degeneration (Balasubramanian et al, 2002). Mutations in the FGFR1 and FGFR2 genes have been shown to cause craniosynostotic aberrations such as Apert-, Pfeiffer-, Jackson-, Weiss-and Crouzon syndrome (Muenke and Schell, 1995).…”
mentioning
confidence: 99%
“…The allele and genotype distributions of the polymorphism were in close agreement with those previously published for healthy Caucasian individuals. [8,11,12,[15][16][17][18][19][20][21][22] In a previous study among 500 Caucasian breast cancer cases and 500 controls, Krippl et al have shown a decreased risk of breast cancer in individuals who were +936 T allele carriers. [9] However, the genotypes in patients did not follow the Hardy-Weinberg equilibrium.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, no association between the +936(C/T) polymorphism and risk to breast cancer among 862 cases and 713 controls could be observed. [21] Here, we did a case-control study of 75 women with breast cancer. We observed no differences in the allele or genotype frequencies between breast cancer case and control groups, (odds ratio, 1.26; 95% confidence interval, 0.50-1.00; P = 0.715).…”
Section: Discussionmentioning
confidence: 99%